An aptasensor based on cobalt oxyhydroxide nanosheets for the detection of thrombin. Issue 39 (16th September 2016) - Yang, Yuan; Cen, Yao; Deng, Wen-Jing; Yu, Ru-Qin; Chen, Ting-Ting; Chu, Xia
Abstract : An aptasensor based on a fluorophore-labelled aptamer and cobalt oxyhydroxide (CoOOH) nanosheets was developed for determining the concentration of thrombin. Abstract : An aptasensor based on a fluorophore-labelled aptamer and cobalt oxyhydroxide (CoOOH) nanosheets was developed for determining the concentration of thrombin. We first found that the CoOOH nanosheets had the ability to distinguish a G-quadruplex from single-stranded DNA (ssDNA) due to the different abilities of the nanosheet to absorb these two DNA forms. The absorption of 6-carboxyfluorescein (6-FAM) labelled aptamer (ssDNA) on the surface of the CoOOH nanosheets resulted in the quenching of the fluorescence of the FAM through fluorescence resonance energy transfer (FRET) between the FAM and the CoOOH nanosheets. However, the binding of the aptamer to its target resulted in the formation of an antiparallel G-quadruplex complex, for which the CoOOH nanosheets had weak affinity, resulting in a recovery of fluorescence. We applied this strategy to the detection of thrombin. The intensity of the fluorescence recovery was found to be linear with the logarithm of the thrombin concentration in the range of 0.5 to 100 nM, and the limit of detection (LOD) was determined to be 0.5 nM. Because of the high selectivity of the aptamer and strong quenching ability of the CoOOH nanosheets, similar aptasensors but with different specific aptamers may potentially serve as platforms to detect a wide range of analytes, and may hence have promising applications in clinical diagnosis.